The Effect of Business Risk, Company Size, Investment Decisions, Board Size, Profitability on Capital Structure in Property and Real Estate Companies for the Period 2018 - 2022 - Kamaluddin, Natalia Angela; Wijoyo, Amin (LPPPIPublishing, 2024)
This study aims to determine the impact of Business Risk, Firm Size, Investment Decisions, Board Size, and Profitability on Capital Structure in property and real estate sector companies listed on the Indonesia Stock Exchange. This study used a sample of 12 companies during the period 2018 - 2022 with a total of 60 data. In this study there are research methods which include Descriptive Statistics, Classical Assumption Test, Multiple linear regression analysis, T test, F test, and Coefficient of determination. Based on the results of the research analysis, it shows that the business risk, investment decision, and profitability variables have a negative and significant effect on the capital structure. Company size variable have no significant influence on capital structure. While the board size variable has a positive and significant effect on capital structure.